Contagious Consumption: Commodity Debates Over The Eighteenth And Nineteenth Century China Trade - Bayer, Kristin (Penerbit Universiti Sains Malaysia (USM Press), 2012)
In the late-eighteenth and early-nineteenth centuries, tea and opium were inextricably linked through what was known as the China trade. As significant stimulant commodities on the global market, they were extremely profitable and also capable of introducing foreign cultural behaviour and social effect into their respective foreign markets.